Vulcanization type catalyst, hydrogenation catalyst, preparation method of hydrogenation catalyst and application of hydrogenation catalyst
By adding Group VIB, Lanthanide and Group VIII metal elements to the hydrogenation catalyst and forming a tower structure through vulcanization treatment, the problem of low activity of the existing catalyst is solved, and efficient hydrogenation activity and stability are achieved.
Patent Information
- Application Number
- CN202311146075.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2023-09-06
- Publication Date
- 2025-03-07
- Estimated Expiration
- 2043-09-06
AI Technical Summary
The existing hydrogenation catalysts have low activity and are difficult to meet the needs of medium and high activity and stability of heavy petroleum products.
A catalyst containing Group VIB metal elements, Lanthanide metal elements and Group VIII metal elements is used, and the active phase is made into a tower-shaped structure by vulcanization treatment to improve the hydrogenation activity and stability of the catalyst.
It achieves high hydrogenation activity and high desulfurization and nitrogen removal rate. The catalyst is used under mild conditions and has a long life. It is suitable for applications such as ethylene tar hydrorefining.
Smart Images

Figure CN119565627A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the field of hydrogenation catalysts, and in particular to a sulfidation catalyst, a hydrogenation catalyst, a preparation method thereof, and applications of the catalyst. Background Art
[0002] As crude oil becomes increasingly inferior and heavier, and society's requirements for the quality of petroleum products are increasing, the hydrogenation process has become a very important link in the oil refining industry. More than 80% of petroleum products have undergone the hydrogenation process.
[0003] Hydrogenation catalysts are mainly composed of metal components and carriers. The metal components are mostly group VIB and group VIII metals, such as W, Mo, Co, Ni, etc. The carriers are Al2O3, TiO2, zeolite, activated carbon, clay and diatomaceous earth, etc. The metal components are loaded on the porous carrier in the form of oxidation to promote reactions such as hydrodenitrogenation, hydrodesulfurization, hydrodemetallization, olefin hydrogenation saturation and hydrocracking. Theoretical research and production experience have shown that the main causes of deactivation of hydrogenation catalysts are carbon deposition, metal deposition caused by raw material degradation and aggregation of active phases during the preparation process. The intensification of raw material degradation and the continuous upgrading of oil quality require hydrogenation catalysts to have higher activity and stability. How to improve the activity and stability of catalysts through the optimization of carrier properties, impregnation solution formula, catalyst preparation technology and sulfurization process, improve the diffusion performance and sol capacity of catalysts, and improve the dispersion of catalyst active phases, reduce aggregation and poisoning are key technologies to improve catalyst activity and stability.
[0004] CN1175481A discloses an impregnation solution for preparing a hydrocracking catalyst, which comprises 25-65 g WO3 / 100 ml solution, 3-20 g NiO / 100 ml solution, and at least one organic acid or ammonium salt in an amount of 0.5-15 g / 100 ml solution.
[0005] CN102836725A discloses a method for preparing a catalyst with high hydrogenation activity. The method comprises first kneading and extruding a solid compound containing a VIII group metal with alumina to obtain an alumina composite containing a VIII group metal with a high specific surface area, then hydrothermally reacting with a salt solution of a VIB group metal, urea and a reaction aid in an autoclave, and finally drying and calcining to obtain a hydrogenation refining catalyst. Compared with the traditional impregnation catalyst, the catalyst prepared by the method of the present invention generates a new type of metal active phase precursor through a carrier surface reaction, which is more easily sulfurized into a II type Co(Ni)-Mo(W)-S phase with higher hydrogenation activity, while reducing the formation of spinel without hydrogenation activity, thereby greatly improving the hydrodesulfurization and hydrodenitrogenation activity of the catalyst, and is particularly suitable for deep hydrorefining of inferior high-sulfur distillate oil. Compared with the prior art, the catalyst provided by the invention adopts the kneading and extrusion molding method and the calcination temperature is relatively low, so the proportion of small pores and super-large pores in the obtained catalyst is high, which can easily cause uneven distribution and insufficient utilization of active components. Therefore, in actual industrial applications, the activity is prone to rapid decline.
[0006] CN102397796A discloses an impregnation solution and a method for preparing a catalyst using the impregnation solution, wherein the impregnation solution contains a compound containing a metal of group VIB, an organic acid salt containing a metal of group VIII, an inorganic acid and an organic acid additive, wherein the concentration of the organic additive in the impregnation solution is 1-150 g / L, and the concentration of the compound containing a metal of group VIB is 100-1100 g / L, the concentration of the organic acid salt containing a metal of group VIII is 10-800 g / L, and the concentration of the inorganic acid is 1-100 g / L in terms of oxide. The impregnation solution provided by the impregnation solution is used to prepare a hydrogenation catalyst, and the catalyst performance is improved, especially the hydrogenation catalytic activity for heavy aromatic hydrocarbons is significantly improved.
[0007] Although the above method improves the performance of hydrogenation catalysts to a certain extent, it is difficult to completely load the active components on the carrier when preparing catalysts with high metal loadings. Even if the active components achieve a high loading, their dispersion is poor, which limits the improvement of catalyst activity. Summary of the invention
[0008] The purpose of the present invention is to overcome the problem of low activity of hydrogenation catalysts in the prior art, and to provide a sulfided catalyst, a hydrogenation catalyst, a preparation method thereof and an application of the catalyst, wherein the catalyst has the characteristics of good hydrogenation activity and high desulfurization and denitrification rate.
[0009] In order to achieve the above-mentioned object, the first aspect of the present invention provides a hydrogenation catalyst, which comprises an active phase and a carrier, wherein the active phase comprises a Group VIB metal element, a lanthanide metal element and a Group VIII metal element; after the catalyst is sulfided, the active phase presents a tower-shaped structure.
[0010] The second aspect of the present invention provides a sulfided catalyst, which is obtained by subjecting the hydrogenation catalyst described in the first aspect to sulfidation treatment; the active phase of the sulfided catalyst has a tower-shaped structure.
[0011] A third aspect of the present invention provides a method for preparing a hydrogenation catalyst, the method comprising:
[0012] (1) preparing a Group VIB metal precursor, a lanthanide metal precursor and a first auxiliary agent to form a solution I; preparing a Group VIII metal precursor and optionally a second auxiliary agent to form a solution II; mixing solutions I and II, and adding a third auxiliary agent to obtain a solution III;
[0013] (2) Solution III is contacted with the carrier, cured, dried, and calcined;
[0014] Among them, the first auxiliary agent is an amino compound and / or an inorganic acid; the second auxiliary agent is an organic acid metal complexing agent; the third auxiliary agent is an alcohol and / or a ketone; the concentration of the Group VIII metal precursor in the solution III is above 45g / L, and the concentration of the Group VIB metal precursor is above 140g / L.
[0015] The fourth aspect of the present invention provides an application of the hydrogenation catalyst described in the first aspect and / or the sulfurized catalyst described in the second aspect and / or the catalyst prepared by the preparation method described in the third aspect in the hydrogenation refining of ethylene tar, wherein the hydrogenation catalyst described in the first aspect and / or the catalyst prepared by the preparation method described in the third aspect is subjected to sulfurization treatment before hydrogenation.
[0016] Through the above technical solution, the present invention has the following advantages:
[0017] The hydrogenation catalyst of the present invention has a tower-shaped structure after sulfurization, with active sites such as edges, corners and sides fully exposed, good (condensed ring aromatic hydrocarbon) hydrogenation activity, high desulfurization and denitrification rates, can be used under relatively mild conditions, and has a long service life.
[0018] The preparation method of the present invention comprises the following steps: ① using a first auxiliary agent as a co-solvent to dissolve a Group VIB metal compound to obtain a high metal concentration; ② using a second auxiliary agent to reduce the interaction between the active component and the carrier, delaying the sulfurization of the Group VIII metal, and increasing the sulfurization temperature of the Group VIII metal; ③ using a third auxiliary agent to reduce the viscosity of the impregnation liquid, thereby preparing a hydrogenation catalyst having the characteristics of the present invention; and simultaneously using an optimal curing time and a low-temperature sulfurization time, the performance of the hydrogenation catalyst of the present invention can be further improved.
[0019] When the hydrogenation catalyst of the present invention is used for hydrogenation refining of ethylene tar, the naphthalene conversion rate is not less than 95%, the bromine value of the hydrogenation product is less than 0.5gBr / 100goil, the tetralin selectivity is 99%, and the sulfur and nitrogen contents are less than 1ppm. The obtained product can be used as a high-quality raw material for producing BTX, realizing the upgrading of oil products to chemical products, greatly improving the added value of the product, and the catalyst has good stability. BRIEF DESCRIPTION OF THE DRAWINGS
[0020] Figure 1 is a TEM image of the sulfided catalyst in Example 1;
[0021] Figure 2 is a TEM image of the sulfided catalyst in Example 6;
[0022] Figure 3 is a TEM image of the sulfided catalyst in Comparative Example 2;
[0023] Figure 4 is a TEM image of the sulfided catalyst in Comparative Example 3;
[0024] Figure 5 is a TPR diagram of the catalysts of Example 1 and Example 5;
[0025] Figure 6 is a TEM image of the sulfided catalyst in Comparative Example 1;
[0026] Figure 7 is a TEM image of the sulfided catalyst in Example 10;
[0027] Figure 8 This is the catalyst stability curve in Example 1. DETAILED DESCRIPTION
[0028] The endpoints and any values of the ranges disclosed in this article are not limited to the precise ranges or values, and these ranges or values should be understood to include values close to these ranges or values. For numerical ranges, the endpoint values of each range, the endpoint values of each range and the individual point values, and the individual point values can be combined with each other to obtain one or more new numerical ranges, which should be considered as specifically disclosed in this article.
[0029] The present invention provides a hydrogenation catalyst, which comprises an active phase and a carrier, wherein the active phase comprises metal elements of Group VIB, lanthanide metal elements and Group VIII metal elements; and the active phase of the catalyst presents a tower-shaped structure after being sulfided.
[0030] The hydrogenation catalyst of the present invention has a tower-shaped structure after sulfurization, and active sites such as edges, corners and sides are fully exposed, the hydrogenation activity of condensed aromatic hydrocarbons is good, the desulfurization and denitrification rates are high, and the catalyst can be used under relatively mild conditions and has a long service life.
[0031] In the present invention, the tower structure is a layered structure shaped like a tower.
[0032] According to a preferred embodiment of the present invention, the number of stacking layers of the tower structure is 3-10 layers, preferably 3-5 layers. By adopting the above preferred scheme, the activity, desulfurization and denitrification rate and service life of the hydrogenation catalyst can be further improved.
[0033] According to a preferred embodiment of the present invention, the stacking layer spacing of the tower structure is 0.2-2 nm. By adopting the above preferred solution, the activity, desulfurization and denitrification rate and service life of the hydrogenation catalyst can be further improved.
[0034] According to a preferred embodiment of the present invention, the stacking length of the tower structure is 3-12 nm, preferably 3-6 nm. By adopting the above preferred solution, the activity, desulfurization and denitrification rate and service life of the hydrogenation catalyst can be further improved.
[0035] In the present invention, after sulfurization, the VIB group metal element obtains a tower structure with this characteristic, which can provide sufficient edges, sides and corners. After sulfurization, the VIII group metal element can be evenly dispersed in these edges, sides and corners to improve the catalytic performance.
[0036] In the present invention, there is no special requirement for the mass content of the active phase and the carrier in the catalyst. According to a preferred embodiment of the present invention, the mass content of the active phase in the catalyst is 15%-60%, preferably 18%-55%; the mass content of the carrier is 40%-85%, preferably 45%-82%. By adopting the above preferred scheme, the activity, desulfurization and denitrification rate and service life of the hydrogenation catalyst can be further improved.
[0037] In the present invention, there is no particular restriction on the mass ratio of the metal element of Group VIB to the metal element of Group VIII in the active phase. According to a preferred embodiment of the present invention, the mass ratio of the metal element of Group VIB to the metal element of Group VIII in the active phase, calculated as oxide, is 0.1-15, preferably 0.8-12. By adopting the above preferred scheme, the activity, desulfurization and denitrification rate and service life of the hydrogenation catalyst can be further improved.
[0038] According to a preferred embodiment of the present invention, the content of lanthanide metal elements in the active phase is 0.1-0.5 wt % calculated as oxide.
[0039] In the present invention, the Group VIB metal element may be a conventional choice in the art. According to a preferred embodiment of the present invention, the Group VIB metal element is selected from Mo, W, Cr, preferably Mo and / or W. By adopting the above preferred scheme, the activity, desulfurization and denitrification rate and service life of the hydrogenation catalyst can be further improved.
[0040] In the present invention, the Group VIII metal element may be a conventional choice in the art. According to a preferred embodiment of the present invention, the Group VIII metal element is selected from Fe, Co, Ni, Pt, Pd, preferably Ni and / or Co. By adopting the above preferred embodiment, the activity, desulfurization and denitrification rate and service life of the hydrogenation catalyst can be further improved.
[0041] According to a preferred embodiment of the present invention, the lanthanide metal element is La and / or Ce.
[0042] In the present invention, the first carrier can be a conventional choice in the art. According to a preferred embodiment of the present invention, the carrier is selected from at least one of Al2O3, Al2O3-TiO2, Al2O3-TiO2-SiO2, and Al2O3-SiO2, preferably selected from at least one of Al2O3, Al2O3-TiO2, and Al2O3-TiO2-SiO2. By adopting the above preferred scheme, the activity, desulfurization and denitrification rate, and service life of the hydrogenation catalyst can be further improved.
[0043] The invention provides a sulfidation catalyst, which is obtained by subjecting the hydrogenation catalyst to sulfidation treatment; the active phase of the sulfidation catalyst presents a tower-shaped structure.
[0044] The tower structure has 3-10 stacking layers, preferably 3-5 layers; and / or a stacking layer spacing of 0.2-2 nm; and / or a stacking length of 3-12 nm, preferably 3-6 nm.
[0045] The sulfided catalyst of the present invention has good hydrogenation activity and high desulfurization and denitrification rate, can be used under relatively mild conditions, and has a long service life.
[0046] The present invention provides a method for preparing a hydrogenation catalyst, the method comprising:
[0047] (1) preparing a Group VIB metal precursor, a lanthanide metal precursor and a first auxiliary agent to form a solution I; preparing a Group VIII metal precursor and optionally a second auxiliary agent to form a solution II; mixing solutions I and II, and adding a third auxiliary agent to obtain a solution III;
[0048] (2) Solution III is contacted with the carrier, cured, dried, and calcined;
[0049] Wherein, the first auxiliary agent is an amino compound and / or an inorganic acid; the second auxiliary agent is an organic acid metal complexing agent; the third auxiliary agent is an alcohol and / or a ketone;
[0050] The concentration of the Group VIII metal precursor in the solution III is above 45 g / L, and the concentration of the Group VIB metal precursor is above 140 g / L.
[0051] The hydrogenation catalyst prepared by the preparation method of the present invention has the following characteristics: ① using the first auxiliary agent as a cosolvent to dissolve the Group VIB metal compound to obtain a high metal concentration; ② using the second auxiliary agent to reduce the interaction between the active component and the carrier, delaying the sulfurization of the Group VIII metal, and increasing the sulfurization temperature of the Group VIII metal; ③ the third auxiliary agent reduces the viscosity of the impregnation liquid, and a hydrogenation catalyst having the characteristics of the present invention can be prepared; after sulfurization, it has a tower-shaped structure, and the active sites such as edges, corners, and edges are fully exposed, the hydrogenation activity of condensed aromatic hydrocarbons is good, the desulfurization and denitrification rate is high, and it can be used under relatively mild conditions and has a long service life. At the same time, the preferred curing time and low-temperature sulfurization time are adopted to further improve the performance of the hydrogenation catalyst of the present invention.
[0052] According to a preferred embodiment of the present invention, stirring is adopted when preparing solution I, solution II and solution III, preferably the stirring temperature is 10-100°C, preferably 25-60°C; the stirring speed is 10-200 rpm, preferably 50-160 rpm.
[0053] According to a preferred embodiment of the present invention, the concentration of the Group VIII metal precursor in the solution III is 50-500 g / L, and the concentration of the Group VIB metal precursor is 150-850 g / L. The concentration of the Group VIII metal precursor in the solution III can be, for example, 50 g / L, 100 g / L, 150 g / L, 200 g / L, 250 g / L, 300 g / L, 350 g / L, 400 g / L, 450 g / L, 500 g / L; the concentration of the Group VIB metal precursor in the solution III can be, for example, 150 g / L, 300 g / L, 450 g / L, 600 g / L, 750 g / L, 850 g / L. By adopting the above preferred scheme, the activity, desulfurization and denitrification rate and service life of the hydrogenation catalyst can be further improved.
[0054] According to a preferred embodiment of the present invention, the ratio of the concentration of the Group VIII metal precursor to the concentration of the Group VIB metal precursor in the solution III is 0.1-1.2, more preferably 0.35-1.0. By adopting the above preferred scheme, the activity, desulfurization and denitrification rate and service life of the hydrogenation catalyst can be further improved.
[0055] The metal precursor in the present invention is a soluble salt of the corresponding metal element, for example, the lanthanide metal salt is selected from at least one of lanthanum nitrate, lanthanum acetate, lanthanum oxalate, cerium nitrate and cerium acetate.
[0056] In the present invention, the first auxiliary agent is at least one of an amino compound and an inorganic acid. According to a preferred embodiment of the present invention, the first auxiliary agent is selected from at least one of urea, acetamide, ethylenediamine, ethanolamine, diethanolamine, triethanolamine, phosphoric acid, nitric acid, and sulfuric acid. The lanthanide metal is selected from at least one of lanthanum nitrate, lanthanum acetate, lanthanum oxalate, cerium nitrate, and cerium acetate. By adopting the above preferred embodiment, the activity, desulfurization and denitrification rate, and service life of the hydrogenation catalyst can be further improved.
[0057] In the present invention, the second auxiliary agent is an organic acid. According to a preferred embodiment of the present invention, the second auxiliary agent is selected from at least one of 1,2-cyclohexanediaminetetraacetic acid, citric acid, tartaric acid, ethylenediaminetetraacetic acid, salicylic acid, and aminotriacetic acid. By adopting the above preferred embodiment, the activity, desulfurization and denitrification rate, and service life of the hydrogenation catalyst can be further improved.
[0058] In the present invention, the third auxiliary agent is an alcohol and / or a ketone. According to a preferred embodiment of the present invention, the third auxiliary agent is a mixture of an alcohol and a ketone, and preferably the mass ratio of the alcohol to the ketone in the mixture is 0.05-2, and more preferably 0.5-1.5; more preferably, the third auxiliary agent is selected from a mixture of ethylene glycol and / or ethanol and acetone and / or 2-butanone. By adopting the above preferred scheme, the activity, desulfurization and denitrification rate and service life of the hydrogenation catalyst can be further improved.
[0059] In the present invention, as long as the purpose of the present invention can be achieved, there is no particular limitation on the molar ratio of the first auxiliary agent to the metal atom of the Group VIB. According to a preferred embodiment of the present invention, the molar ratio of the first auxiliary agent to the metal atom of the Group VIB is 0.1-1.2, for example, it can be 0.1, 0.15, 0.2, 0.25, 0.3, 0.35, 0.4, 0.45, 0.5, 0.55, 0.6, 0.65, 0.7, 0.75, 0.8, 0.85, 0.9, 0.95, 1.0, 1.05, 1.1, 1.15, 1.20; preferably 0.25-1.0. By adopting the above preferred scheme, the activity, desulfurization and denitrification rate and service life of the hydrogenation catalyst can be further improved.
[0060] In the present invention, as long as the purpose of the present invention can be achieved, there is no particular limitation on the molar ratio of the second additive to the Group VIII metal atom. According to a preferred embodiment of the present invention, the molar ratio of the second additive to the Group VIII metal atom is 0.05-1.2, for example, 0.05, 0.1, 0.15, 0.2, 0.25, 0.3, 0.35, 0.4, 0.45, 0.5, 0.55, 0.6, 0.65, 0.7, 0.75, 0.8, 0.85, 0.9, 0.95, 1.0, 1.05, 1.1, 1.15, 1.20; preferably 0.14-0.8. By adopting the above preferred embodiment, the activity, desulfurization and denitrification rate and service life of the hydrogenation catalyst can be further improved.
[0061] In the present invention, there is no particular limitation on the mass ratio of the solution III and the carrier when they are in contact in step (2). According to a preferred embodiment of the present invention, in step (2), the solution III and the carrier are in contact at a mass ratio of 0.5-2.5; preferably 1.0-2.0.
[0062] According to a preferred embodiment of the present invention, the carrier is selected from at least one of Al2O3, Al2O3-TiO2, Al2O3-TiO2-SiO2, and Al2O3-SiO2, preferably selected from at least one of Al2O3, Al2O3-TiO2, and Al2O3-TiO2-SiO2.
[0063] According to a preferred embodiment of the present invention, the Group VIB metal element is selected from Mo, W, Cr, preferably Mo and / or W.
[0064] According to a preferred embodiment of the present invention, the Group VIII metal element is selected from Fe, Co, Ni, Pt, Pd, preferably Ni and / or Co.
[0065] According to a preferred embodiment of the present invention, the lanthanide metal element is La and / or Ce.
[0066] According to a preferred embodiment of the present invention, the contact conditions include: the contact temperature is 0-60°C, preferably 20-40°C.
[0067] According to a preferred embodiment of the present invention, the contact conditions include: the contact time is 5-60 min, preferably 8-40 min.
[0068] According to a preferred embodiment of the present invention, the health-preserving conditions include: a health-preserving temperature of 0-60° C., preferably 20-40° C.; and / or
[0069] According to a preferred embodiment of the present invention, the health-preserving conditions include: the health-preserving time is 2-96h, preferably 6-48h.
[0070] According to a preferred embodiment of the present invention, the drying conditions include: a drying temperature of 50-130°C, preferably 60-120°C.
[0071] According to a preferred embodiment of the present invention, the drying conditions include: drying time is 3-46 hours, preferably 6-36 hours.
[0072] According to a preferred embodiment of the present invention, the drying conditions include: air volume velocity 2-250h -1 , preferably 20-150h -1 .
[0073] According to a preferred embodiment of the present invention, the calcination conditions include: a calcination temperature of 150-520°C, preferably 280-500°C.
[0074] According to a preferred embodiment of the present invention, the calcination conditions include: the calcination time is 2-24 hours, preferably 3-12 hours.
[0075] According to a preferred embodiment of the present invention, the roasting conditions include: air volume space velocity 2-250h -1 , preferably 25-150h -1 .
[0076] The present invention provides an application of the hydrogenation catalyst and / or the sulfurized catalyst and / or the catalyst prepared by the preparation method in the hydrogenation of crude oil. Before hydrogenation, the hydrogenation catalyst and / or the catalyst prepared by the preparation method is subjected to sulfurization treatment.
[0077] According to a preferred embodiment of the present invention, the hydrogenation conditions include: inlet temperature of 200-270°C, reaction pressure of 2.3-6.0MPa, hydrogen-to-oil volume ratio (hydrogen to feedstock oil volume ratio) of 400-1500, liquid phase volume space velocity of 0.2-1.8h -1 .
[0078] According to a preferred embodiment of the present invention, the vulcanization conditions include: the vulcanizing agent contains 0.05-2wt% sulfur; and / or the vulcanization temperature is 120-380°C; and / or the vulcanization time is 8-72h; and / or the vulcanizing agent volume space velocity is 0.3-3h -1 ; and / or the hydrogen-to-oil volume ratio (the volume ratio of hydrogen and sulfiding agent) is 300-2000; and / or the sulfiding pressure is 0.5-10.0MPa;
[0079] According to a preferred embodiment of the present invention, the vulcanization temperature is 150-360°C; and / or the vulcanization time is 8-56 hours; and / or the vulcanizing agent volume space velocity is 0.5-1.5h -1 ; and / or the hydrogen-to-oil volume ratio (volume ratio of hydrogen and sulfiding agent) is 500-1500; and / or the sulfiding pressure is 1.0-6.0MPa.
[0080] According to a preferred embodiment of the present invention, vulcanization is carried out in a programmed temperature manner, including: an initial temperature of 25-150°C, a heating rate of 5-15°C / min, a step temperature interval of 50-80°C, a step temperature holding time of 4-10h, a final temperature of 320-360°C, and a final temperature treatment time of 27-35h;
[0081] According to a preferred embodiment of the present invention, the feedstock oil is selected from the product of ethylene tar after weight removal and one-stage hydrogenation to olefins.
[0082] The present invention will be described in detail below by way of examples. In the following examples:
[0083] The catalyst structure characteristics and metal nanoparticle size were tested using a G2F30 transmission electron microscope (TEM) from FEI, USA. The element composition on the catalyst was determined using a ZSX-100e 4580 X-ray fluorescence spectrometer from Rigaku Corporation, Japan.
[0084] The nitrogen and sulfur test was carried out on the Antek900 sulfur and nitrogen instrument. The nitrogen content test method refers to the standard SH / T0657-2007 (chemiluminescence method); the sulfur content test method refers to the standard SH / T0689-2000 (ultraviolet fluorescence method)
[0085] The naphthalene conversion rate and tetralin selectivity in the product are calculated as follows:
[0086]
[0087]
[0088] All raw materials are commercially available.
[0089] Example 1
[0090] 1. Weigh 720g of ammonium metatungstate, 130g of ammonium molybdate, and 15g of lanthanum nitrate, dissolve in 500g of deionized water, add 57g of phosphoric acid, and stir at room temperature for 30 minutes to obtain aqueous solution I; weigh 250g of nickel nitrate and 42.5g of 1,2-cyclohexanediaminetetraacetic acid, dissolve in 200g of deionized water, and stir at room temperature for 30 minutes to obtain aqueous solution II, mix aqueous solution I and aqueous solution II, add 54g of ethylene glycol and 27g of 2-butanone, dilute to 1L with deionized water, and continue stirring at room temperature for 30 minutes to obtain solution III. The concentration of the Group VIB metal precursor in the solution III is 850g / L, the concentration of the Group VIII metal precursor is 250g / L, the molar ratio of the first auxiliary agent to the Group VIB metal atom is 1.0; the molar ratio of the second auxiliary agent to the Group VIII metal atom is 0.14. The mass ratio of ethylene glycol to 2-butanone in the third auxiliary agent is 2.
[0091] 2. Preparation of catalyst
[0092] Take 1000 g of Al2O3-TiO2-SiO2 carrier (including Al2O3, 97%, TiO2, 1.5%; SiO2, 1.5%) into a rotating pan, slowly add solution III prepared in 1, rotate the pan at 58 rpm, and soak for 10 minutes.
[0093] Curing: Curing the impregnated carrier at 30°C for 48 hours.
[0094] Drying, air atmosphere, starting at 25°C, heating at 10°C / hour to 70°C, maintaining constant temperature for 8 hours, heating at 10°C / hour to 110°C, maintaining constant temperature for 4 hours.
[0095] Calcination was carried out in air atmosphere, starting at 25°C, increasing the temperature at 140°C / hour to 445°C, and maintaining the temperature for 3 hours.
[0096] The catalyst composition is shown in Table 1.
[0097] 3. Catalyst sulfidation and evaluation
[0098] The catalyst prepared in 2 was loaded into the fixed bed reactor and sulfurization was started after the airtightness was qualified. Under the system pressure of 5.5Mpa, the hydrogen volume space velocity was 800h -1 Hydrogen was introduced and the temperature was raised from room temperature to 150°C at a rate of 30°C / h. -1 A vulcanizing agent containing 0.5 wt% sulfur was introduced, and the temperature was raised to 180°C at 5°C / h for 6h, kept constant for 5h, and then raised to 230°C at 5°C / h for 10h, kept constant for 4h, and then raised to 280°C at 10°C / h for 5h, kept constant for 4h, and then raised to 320°C at 10°C / h for 4h, and kept constant for 2h, and the catalyst vulcanization was completed. The catalyst after vulcanization was tested using a G2F30 transmission electron microscope (TEM) from FEI Company of the United States to obtain TEM Figure 1From the figure, it can be seen that the active phase of the sulfide catalyst has a tower-shaped structure, with 3-5 stacking layers; the stacking layer spacing is 0.2-2nm; and the stacking length is 3-6nm.
[0099] The temperature was lowered to 240°C, the pressure was lowered to 3.0 MPa, and the hydrogenation product after de-weighting and diene removal was introduced. The H2 / Oil molar ratio was 1000, and the raw material liquid phase volume space velocity was 0.8 h -1 .
[0100] The evaluation results of the catalyst are listed in Table 2. The catalyst stability curve is shown in Table 2. Figure 8 shown.
[0101] Example 2
[0102] 1. Weigh 320g of ammonium metatungstate, 105g of ammonium molybdate, and 15g of lanthanum nitrate, dissolve in 400g of deionized water, add 23.6g of phosphoric acid, and stir at room temperature for 30 minutes to obtain aqueous solution I; weigh 400g of nickel nitrate and 190g of 1,2-cyclohexanediaminetetraacetic acid, dissolve in 400g of deionized water, and stir at room temperature for 30 minutes to obtain aqueous solution II, mix aqueous solution I and aqueous solution II, add 27g of ethylene glycol and 27g of 2-butanone, dilute to 1L with deionized water, and continue stirring at room temperature for 30 minutes to obtain solution III. The concentration of the Group VIB metal precursor in the solution III is 425g / L, the concentration of the Group VIII metal precursor is 400g / L, the molar ratio of the first auxiliary agent to the Group VIB metal atom is 0.6; the molar ratio of the second auxiliary agent to the Group VIII metal atom is 0.4. The mass ratio of ethylene glycol to 2-butanone in the third auxiliary agent is 1.
[0103] 2. Preparation of catalyst
[0104] Take 1000 g of Al2O3-TiO2-SiO2 carrier (including Al2O3, 97%, TiO2, 1.5%; SiO2, 1.5%) into a rotating pan, slowly add solution III prepared in 1, rotate the pan at 58 rpm, and soak for 10 minutes.
[0105] Curing: Curing the impregnated carrier at room temperature for 48 hours.
[0106] Drying, starting from room temperature, air atmosphere, heating to 70°C at 10°C / hour, keeping constant temperature for 8 hours, heating to 110°C at 10°C / hour, keeping constant temperature for 4 hours.
[0107] Calcination started at room temperature, in air atmosphere, and the temperature was increased from 140°C / hour to 445°C, and kept constant for 3 hours.
[0108] The catalyst composition is shown in Table 1.
[0109] 3. Catalyst sulfidation and evaluation
[0110] The catalyst prepared in 2 was loaded into a fixed bed reactor and sulfurization was started after the airtightness was qualified. Under the system pressure of 5.5 MPa, the hydrogen volume space velocity was 800 h -1 Hydrogen was introduced and the temperature was raised from room temperature to 150°C at a rate of 30°C / h. -1 A vulcanizing agent containing 0.5 wt% sulfur was introduced, and the temperature was raised to 180°C at 5°C / h for 6h, kept constant for 5h, then raised to 230°C at 5°C / h for 10h, kept constant for 4h, then raised to 280°C at 10°C / h for 5h, kept constant for 4h, then raised to 320°C at 10°C / h for 4h, kept constant for 2h, and the catalyst vulcanization was completed. The catalyst after vulcanization was tested using a G2F30 transmission electron microscope (TEM) from FEI Company of the United States to obtain a TEM image, which was consistent with the Figure 1 Similarly, it can be seen from the figure that the active phase of the sulfide catalyst presents a tower-shaped structure with 3-5 stacking layers; the stacking layer spacing is 0.2-2nm; and the stacking length is 3-6nm.
[0111] The temperature was lowered to 240°C, the pressure was lowered to 3.0 MPa, and the hydrogenation product after de-weighting and diene removal was introduced. The H2 / Oil molar ratio was 1000, and the raw material liquid phase volume space velocity was 0.8 h -1 .
[0112] The evaluation results of the catalyst are listed in Table 2.
[0113] Example 3
[0114] 1. Weigh 400g of ammonium metatungstate, 100g of ammonium molybdate, and 15g of lanthanum nitrate, dissolve in 400g of deionized water, add 10.2g of phosphoric acid, and stir at room temperature for 30 minutes to obtain aqueous solution I; weigh 500g of nickel nitrate and 475g of 1,2-cyclohexanediaminetetraacetic acid, dissolve in 400g of deionized water, and stir at room temperature for 30 minutes to obtain aqueous solution II, mix aqueous solution I and aqueous solution II, add 54g of ethylene glycol and 27g of 2-butanone, and dilute to 1L with deionized water, and continue to stir at room temperature for 30 minutes to obtain solution III. The concentration of the Group VIB metal precursor in the solution III is 500g / L, the concentration of the Group VIII metal precursor is 500g / L, the molar ratio of the first auxiliary agent to the Group VIB metal atom is 0.25; the molar ratio of the second auxiliary agent to the Group VIII metal atom is 0.8. The mass ratio of ethylene glycol to 2-butanone in the third auxiliary agent is 2.
[0115] 2. Preparation of catalyst
[0116] Take 100 g of alumina support and put it in a rotating pan. Slowly add solution III prepared in step 1. The rotating speed of the rotating pan is 58 rpm and the mixture is immersed for 10 minutes.
[0117] Curing: Curing the impregnated carrier at room temperature for 48 hours.
[0118] Drying, starting from room temperature, air atmosphere, heating to 70°C at 10°C / hour, keeping constant temperature for 8 hours, heating to 110°C at 10°C / hour, keeping constant temperature for 4 hours.
[0119] Calcination started at room temperature, in air atmosphere, and the temperature was increased from 140°C / hour to 445°C, and kept constant for 3 hours.
[0120] The catalyst composition is shown in Table 1.
[0121] 3. Catalyst sulfidation and evaluation
[0122] The catalyst prepared in 2 was loaded into a fixed bed reactor and sulfurization was started after the airtightness was qualified. Under the system pressure of 5.5 MPa, the hydrogen volume space velocity was 800 h -1 Hydrogen was introduced and the temperature was raised from room temperature to 150°C at a rate of 30°C / h. -1 A vulcanizing agent containing 0.5 wt% sulfur was introduced, and the temperature was raised to 180°C at 5°C / h for 6h, kept constant for 5h, then raised to 230°C at 5°C / h for 10h, kept constant for 4h, then raised to 280°C at 10°C / h for 5h, kept constant for 4h, then raised to 320°C at 10°C / h for 4h, kept constant for 2h, and the catalyst vulcanization was completed. The catalyst after vulcanization was tested using a G2F30 transmission electron microscope (TEM) from FEI Company of the United States to obtain a TEM image, which was consistent with the Figure 1 Similarly, it can be seen from the figure that the active phase of the sulfide catalyst presents a tower-shaped structure with 3-5 stacking layers; the stacking layer spacing is 0.2-2nm; and the stacking length is 3-6nm.
[0123] The temperature was lowered to 240°C, the pressure was lowered to 3.0 MPa, and the hydrogenation product after de-weighting and diene removal was introduced. The H2 / Oil molar ratio was 1000, and the raw material liquid phase volume space velocity was 0.8 h -1 .
[0124] The evaluation results of the catalyst are listed in Table 2.
[0125] Example 4
[0126] 1. Weigh 720g of ammonium metatungstate, 130g of ammonium molybdate, and 15g of lanthanum nitrate, dissolve in 500g of deionized water, add 18g of urea and 28g of phosphoric acid, and stir at room temperature for 30 minutes to obtain aqueous solution I; weigh 250g of nickel nitrate and 42.5g of 1,2-cyclohexanediaminetetraacetic acid, dissolve in 200g of deionized water, and stir at room temperature for 30 minutes to obtain aqueous solution II, mix aqueous solution I and aqueous solution II, add 54g of ethylene glycol and 27g of 2-butanone, and dilute to 1L with deionized water, and continue to stir at room temperature for 30 minutes to obtain solution III. The concentration of the Group VIB metal precursor in the solution III is 850g / L, the concentration of the Group VIII metal precursor is 250g / L, the molar ratio of the first auxiliary agent to the Group VIB metal atom is 1.0; the molar ratio of the second auxiliary agent to the Group VIII metal atom is 0.14. The mass ratio of ethylene glycol to 2-butanone in the third auxiliary agent is 2.
[0127] 2. Preparation of catalyst
[0128] Take 1000 g of Al2O3-TiO2-SiO2 carrier (including Al2O3, 97%, TiO2, 1.5%; SiO2, 1.5%) into a rotating pan, slowly add solution III prepared in 1, rotate the pan at 58 rpm, and soak for 10 minutes.
[0129] Curing: Curing the impregnated carrier at 30°C for 48 hours.
[0130] Drying, air atmosphere, starting at 25°C, heating at 10°C / hour to 70°C, maintaining constant temperature for 8 hours, heating at 10°C / hour to 110°C, maintaining constant temperature for 4 hours.
[0131] Calcination was carried out in air atmosphere, starting at 25°C, increasing the temperature at 140°C / hour to 445°C, and maintaining the temperature for 3 hours.
[0132] The catalyst composition is shown in Table 1.
[0133] 3. Catalyst sulfidation and evaluation
[0134] The catalyst prepared in 2 was loaded into a fixed bed reactor and sulfurization was started after the airtightness was qualified. Under the system pressure of 5.5 MPa, the hydrogen volume space velocity was 800 h -1Hydrogen is introduced, and the temperature is raised from room temperature to 150°C at a rate of 30°C / h, and a vulcanizing agent containing 0.5wt% sulfur is introduced, and the temperature is raised at 5°C / h for 6h to 180°C, and the temperature is kept constant for 5h, and then the temperature is raised at 5°C / h for 10h to 230°C, and then the temperature is kept constant for 4h. The temperature is raised at 10°C / h for 5h to 280°C, and the temperature is kept constant for 4h. The temperature is raised at 10°C / h for 4h to 320°C, and the temperature is kept constant for 2 hours, and the catalyst vulcanization is completed. The catalyst after vulcanization is tested using a G2F30 transmission electron microscope (TEM) of FEI Company of the United States. It can be seen from the figure that the active phase of the vulcanized catalyst has a tower structure, with 3-5 stacking layers; the stacking layer spacing is 0.2-2nm; and the stacking length is 3-6nm.
[0135] The temperature was lowered to 240°C, the pressure was lowered to 3.0 MPa, and the hydrogenation product after de-weighting and diene removal was introduced. The H2 / Oil molar ratio was 1000, and the raw material liquid phase volume space velocity was 0.8 h -1 .
[0136] The evaluation results of the catalyst are listed in Table 2.
[0137] Example 5
[0138] 1. Weigh 720g of ammonium metatungstate, 130g of ammonium molybdate, and 15g of lanthanum nitrate, dissolve in 500g of deionized water, add 57g of phosphoric acid, and stir at room temperature for 30 minutes to obtain aqueous solution I; weigh 250g of nickel nitrate and 18g of 1,2-cyclohexanediaminetetraacetic acid, dissolve in 200g of deionized water, and stir at room temperature for 30 minutes to obtain aqueous solution II, mix aqueous solution I and aqueous solution II, add 54g of ethylene glycol and 27g of 2-butanone, dilute to 1L with deionized water, and continue stirring at room temperature for 30 minutes to obtain solution III. The concentration of the Group VIB metal precursor in the solution III is 850g / L, the concentration of the Group VIII metal precursor is 250g / L, the molar ratio of the first auxiliary agent to the Group VIB metal atom is 1.0; the molar ratio of the second auxiliary agent to the Group VIII metal atom is 0.057. The mass ratio of ethylene glycol to 2-butanone in the third auxiliary agent is 2.
[0139] 2. Preparation of catalyst
[0140] Take 1000 g of Al2O3-TiO2-SiO2 carrier (including Al2O3, 97%, TiO2, 1.5%; SiO2, 1.5%) into a rotating pan, slowly add solution III prepared in 1, rotate the pan at 58 rpm, and soak for 10 minutes.
[0141] Aging: The impregnated support was aged at 30°C for 48 hours.
[0142] Drying, air atmosphere, starting at 25°C, heating at 10°C / hour to 70°C, maintaining constant temperature for 8 hours, heating at 10°C / hour to 110°C, maintaining constant temperature for 4 hours.
[0143] Calcination was carried out in air atmosphere, starting at 25°C, increasing the temperature at 140°C / hour to 445°C, and maintaining the temperature for 3 hours.
[0144] The catalyst composition is shown in Table 1.
[0145] 3. Catalyst sulfidation and evaluation
[0146] The catalyst prepared in 2 was loaded into a fixed bed reactor and sulfurization was started after the airtightness was qualified. Under the system pressure of 5.5 MPa, the hydrogen volume space velocity was 800 h -1 Hydrogen was introduced, and the temperature was raised from room temperature to 150°C at a rate of 30°C / h. A sulfurizing agent containing 0.5wt% sulfur was introduced, and the temperature was raised at 5°C / h for 6h to 180°C. After keeping the temperature constant for 5h, the temperature was raised at 5°C / h for 10h to 230°C. After keeping the temperature constant for 4h, the temperature was raised at 10°C / h for 5h to 280°C. After keeping the temperature constant for 4h, the temperature was raised at 10°C / h for 4h to 320°C. After keeping the temperature constant for 2 hours, the catalyst sulfurization was completed. The sulfurized catalyst was tested using a G2F30 transmission electron microscope (TEM) from FEI Company of the United States. It can be seen from the figure that the active phase of the sulfurized catalyst has a partial tower-shaped structure, with 3-7 stacking layers; the stacking layer spacing is 0.2-2nm; and the stacking length is 3-12nm. It is just that the reduction peak temperature moves to the high temperature zone, indicating that the interaction between the metal and the carrier is strong. See Figure TPR spectrum ( Figure 5 )
[0147] The temperature was lowered to 240°C, the pressure was lowered to 3.0 MPa, and the hydrogenation product after de-weighting and diene removal was introduced. The H2 / Oil molar ratio was 1000, and the raw material liquid phase volume space velocity was 0.8 h -1 .
[0148] The evaluation results of the catalyst are listed in Table 2.
[0149] Example 6
[0150] 1. Weigh 720g of ammonium metatungstate, 130g of ammonium molybdate, and 15g of lanthanum nitrate, dissolve in 500g of deionized water, add 57g of phosphoric acid, and stir at room temperature for 30 minutes to obtain aqueous solution I; weigh 250g of nickel nitrate and 200g of deionized water, stir at room temperature for 30 minutes to obtain aqueous solution II, mix aqueous solution I and aqueous solution II, add 54g of ethylene glycol and 27g of 2-butanone, dilute to 1L with deionized water, and continue stirring at room temperature for 30 minutes to obtain solution III. The concentration of the Group VIB metal precursor in the solution III is 850g / L, the concentration of the Group VIII metal precursor is 250g / L, the molar ratio of the first auxiliary agent to the Group VIB metal atom is 1.0; the mass ratio of ethylene glycol to 2-butanone is 2.
[0151] 2. Preparation of catalyst
[0152] Take 1000 g of Al2O3-TiO2-SiO2 carrier (including Al2O3, 97%, TiO2, 1.5%; SiO2, 1.5%) into a rotating pan, slowly add solution III prepared in 1, rotate the pan at 58 rpm, and soak for 10 minutes.
[0153] Curing: Curing the impregnated carrier at 30°C for 48 hours.
[0154] Drying, air atmosphere, starting at 25°C, heating at 10°C / hour to 70°C, maintaining constant temperature for 8 hours, heating at 10°C / hour to 110°C, maintaining constant temperature for 4 hours.
[0155] Calcination was carried out in air atmosphere, starting at 25°C, increasing the temperature at 140°C / hour to 445°C, and maintaining the temperature for 3 hours.
[0156] The catalyst composition is shown in Table 1.
[0157] 3. Catalyst sulfidation and evaluation
[0158] The catalyst prepared in 2 was loaded into a fixed bed reactor and sulfurization was started after the airtightness was qualified. Under the system pressure of 5.5 MPa, the hydrogen volume space velocity was 800 h -1 Hydrogen was introduced, and the temperature was raised from room temperature to 150°C at a rate of 30°C / h. A sulfurizing agent containing 0.5 wt% sulfur was introduced, and the temperature was raised at 5°C / h for 6 hours to 180°C. After keeping the temperature constant for 5 hours, the temperature was raised at 5°C / h for 10 hours to 230°C. After keeping the temperature constant for 4 hours, the temperature was raised at 10°C / h for 5 hours to 280°C. After keeping the temperature constant for 4 hours, the temperature was raised at 10°C / h for 4 hours to 320°C. After keeping the temperature constant for 2 hours, the catalyst sulfurization was completed. The catalyst after sulfurization was tested using a G2F30 transmission electron microscope (TEM) from FEI Company of the United States to obtain TEM Figure 2 From the figure, it can be seen that the active phase of the sulfided catalyst has a tower structure, with 4-10 stacking layers, 0.2-2nm stacking layer spacing, and 6-12nm stacking length. Long stacking is not conducive to the formation of enough hydrogenation active centers.
[0159] The temperature was lowered to 240°C, the pressure was lowered to 3.0 MPa, and the hydrogenation product after de-weighting and diene removal was introduced. The H2 / Oil molar ratio was 1000, and the raw material liquid phase volume space velocity was 0.8 h -1 .
[0160] The evaluation results of the catalyst are listed in Table 2.
[0161] Example 7
[0162] 1. Weigh 720g of ammonium metatungstate, 130g of ammonium molybdate, and 15g of lanthanum nitrate, dissolve in 500g of deionized water, add 57g of phosphoric acid, and stir at room temperature for 30 minutes to obtain aqueous solution I; weigh 45g of nickel nitrate and 8.11g of 1,2-cyclohexanediaminetetraacetic acid, dissolve in 200g of deionized water, and stir at room temperature for 30 minutes to obtain aqueous solution II, mix aqueous solution I and aqueous solution II, add 54g of ethylene glycol and 27g of 2-butanone, dilute to 1L with deionized water, and continue stirring at room temperature for 30 minutes to obtain solution III. The concentration of the Group VIB metal precursor in the solution III is 850g / L, the concentration of the Group VIII metal precursor is 45g / L, the molar ratio of the first auxiliary agent to the Group VIB metal atom is 1.0; the molar ratio of the second auxiliary agent to the Group VIII metal atom is 0.14. The mass ratio of ethylene glycol to 2-butanone in the third auxiliary agent is 2.
[0163] 2. Preparation of catalyst
[0164] Take 1000 g of Al2O3-TiO2-SiO2 carrier (including Al2O3, 97%, TiO2, 1.5%; SiO2, 1.5%) into a rotating pan, slowly add solution III prepared in 1, rotate the pan at 58 rpm, and soak for 10 minutes.
[0165] Curing: Curing the impregnated carrier at 30°C for 48 hours.
[0166] Drying, air atmosphere, starting at 25°C, heating at 10°C / hour to 70°C, maintaining constant temperature for 8 hours, heating at 10°C / hour to 110°C, maintaining constant temperature for 4 hours.
[0167] Calcination was carried out in air atmosphere, starting at 25°C, increasing the temperature at 140°C / hour to 445°C, and maintaining the temperature for 3 hours.
[0168] The catalyst composition is shown in Table 1.
[0169] 3. Catalyst sulfidation and evaluation
[0170] The catalyst prepared in 2 was loaded into a fixed bed reactor and sulfurization was started after the airtightness was qualified. Under the system pressure of 5.5 MPa, the hydrogen volume space velocity was 800 h -1 Hydrogen is introduced, and the temperature is raised from room temperature to 150°C at a rate of 30°C / h, and a vulcanizing agent containing 0.5wt% sulfur is introduced, and the temperature is raised at 5°C / h for 6h to 180°C, and the temperature is kept constant for 5h, and then the temperature is raised at 5°C / h for 10h to 230°C, and then the temperature is kept constant for 4h. The temperature is raised at 10°C / h for 5h to 280°C, and the temperature is kept constant for 4h. The temperature is raised at 10°C / h for 4h to 320°C, and the temperature is kept constant for 2 hours, and the catalyst vulcanization is completed. The catalyst after vulcanization is tested using a G2F30 transmission electron microscope (TEM) of FEI Company of the United States. It can be seen from the figure that the active phase of the vulcanized catalyst has a tower structure, with 3-5 stacking layers; the stacking layer spacing is 0.2-2nm; and the stacking length is 3-6nm.
[0171] The temperature was lowered to 240°C, the pressure was lowered to 3.0 MPa, and the hydrogenation product after de-weighting and diene removal was introduced. The H2 / Oil molar ratio was 1000, and the raw material liquid phase volume space velocity was 0.8 h -1 .
[0172] The evaluation results of the catalyst are listed in Table 2.
[0173] Example 8
[0174] 1. Weigh 130g of ammonium metatungstate, 10g of ammonium molybdate, 15g of lanthanum nitrate in 500g of deionized water, add 5g of phosphoric acid, stir at room temperature for 30 minutes to obtain aqueous solution I; weigh 250g of nickel nitrate and 42.5g of 1,2-cyclohexanediaminetetraacetic acid and dissolve in 200g of deionized water, stir at room temperature for 30 minutes to obtain aqueous solution II, mix aqueous solution I and aqueous solution II, add 54g of ethylene glycol and 27g of 2-butanone, dilute to 1L with deionized water, and continue stirring at room temperature for 30 minutes to obtain solution III. The concentration of the Group VIB metal precursor in the solution III is 140g / L, the concentration of the Group VIII metal precursor is 250g / L, the molar ratio of the first auxiliary agent to the Group VIB metal atom is 1.0; the molar ratio of the second auxiliary agent to the Group VIII metal atom is 0.14. The mass ratio of ethylene glycol to 2-butanone in the third auxiliary agent is 2.
[0175] 2. Preparation of catalyst
[0176] Take 1000 g of Al2O3-TiO2-SiO2 carrier (including Al2O3, 97%, TiO2, 1.5%; SiO2, 1.5%) into a rotating pan, slowly add solution III prepared in 1, rotate the pan at 58 rpm, and soak for 10 minutes.
[0177] Curing: Curing the impregnated carrier at 30°C for 48 hours.
[0178] Drying, air atmosphere, starting at 25°C, heating at 10°C / hour to 70°C, maintaining constant temperature for 8 hours, heating at 10°C / hour to 110°C, maintaining constant temperature for 4 hours.
[0179] Calcination was carried out in air atmosphere, starting at 25°C, increasing the temperature at 140°C / hour to 445°C, and maintaining the temperature for 3 hours.
[0180] The catalyst composition is shown in Table 1.
[0181] 3. Catalyst sulfidation and evaluation
[0182] The catalyst prepared in 2 was loaded into a fixed bed reactor and sulfurization was started after the airtightness was qualified. Under the system pressure of 5.5 MPa, the hydrogen volume space velocity was 800 h -1Hydrogen is introduced, and the temperature is raised from room temperature to 150°C at a rate of 30°C / h, and a vulcanizing agent containing 0.5wt% sulfur is introduced, and the temperature is raised at 5°C / h for 6h to 180°C, and the temperature is kept constant for 5h, and then the temperature is raised at 5°C / h for 10h to 230°C, and then the temperature is kept constant for 4h. The temperature is raised at 10°C / h for 5h to 280°C, and the temperature is kept constant for 4h. The temperature is raised at 10°C / h for 4h to 320°C, and the temperature is kept constant for 2 hours, and the catalyst vulcanization is completed. The catalyst after vulcanization is tested using a G2F30 transmission electron microscope (TEM) of FEI Company of the United States. It can be seen from the figure that the active phase of the vulcanized catalyst has a tower structure, with 3-5 stacking layers; the stacking layer spacing is 0.2-2nm; and the stacking length is 3-6nm.
[0183] The temperature was lowered to 240°C, the pressure was lowered to 3.0 MPa, and the hydrogenation product after de-weighting and diene removal was introduced. The H2 / Oil molar ratio was 1000, and the raw material liquid phase volume space velocity was 0.8 h -1 .
[0184] The evaluation results of the catalyst are listed in Table 2.
[0185] Example 9
[0186] 1. Weigh 720g of ammonium metatungstate, 130g of ammonium molybdate, and 15g of lanthanum nitrate, dissolve in 500g of deionized water, add 80g of phosphoric acid, and stir at room temperature for 30 minutes to obtain aqueous solution I; weigh 250g of nickel nitrate and 42.5g of 1,2-cyclohexanediaminetetraacetic acid, dissolve in 200g of deionized water, and stir at room temperature for 30 minutes to obtain aqueous solution II, mix aqueous solution I and aqueous solution II, add 54g of ethylene glycol and 27g of 2-butanone, dilute to 1L with deionized water, and continue stirring at room temperature for 30 minutes to obtain solution III. The concentration of the Group VIB metal precursor in the solution III is 850g / L, the concentration of the Group VIII metal precursor is 250g / L, the molar ratio of the first auxiliary agent to the Group VIB metal atom is 1.4; the molar ratio of the second auxiliary agent to the Group VIII metal atom is 0.14. The mass ratio of ethylene glycol to 2-butanone in the third auxiliary agent is 2.
[0187] 2. Preparation of catalyst
[0188] Take 1000 g of Al2O3-TiO2-SiO2 carrier (including Al2O3, 97%, TiO2, 1.5%; SiO2, 1.5%) into a rotating pan, slowly add solution III prepared in 1, rotate the pan at 58 rpm, and soak for 10 minutes.
[0189] Curing: Curing the impregnated carrier at 30°C for 48 hours.
[0190] Drying, air atmosphere, starting at 25°C, heating at 10°C / hour to 70°C, maintaining constant temperature for 8 hours, heating at 10°C / hour to 110°C, maintaining constant temperature for 4 hours.
[0191] Calcination was carried out in air atmosphere, starting at 25°C, increasing the temperature at 140°C / hour to 445°C, and maintaining the temperature for 3 hours.
[0192] The catalyst composition is shown in Table 1.
[0193] 3. Catalyst sulfidation and evaluation
[0194] The catalyst prepared in 2 was loaded into a fixed bed reactor and sulfurization was started after the airtightness was qualified. Under the system pressure of 5.5 MPa, the hydrogen volume space velocity was 800 h -1 Hydrogen is introduced, and the temperature is raised from room temperature to 150°C at a rate of 30°C / h, and a vulcanizing agent containing 0.5wt% sulfur is introduced, and the temperature is raised at 5°C / h for 6h to 180°C, and the temperature is kept constant for 5h, and then the temperature is raised at 5°C / h for 10h to 230°C, and then the temperature is kept constant for 4h. The temperature is raised at 10°C / h for 5h to 280°C, and the temperature is kept constant for 4h. The temperature is raised at 10°C / h for 4h to 320°C, and the temperature is kept constant for 2 hours, and the catalyst vulcanization is completed. The catalyst after vulcanization is tested using a G2F30 transmission electron microscope (TEM) of FEI Company of the United States. It can be seen from the figure that the active phase of the vulcanized catalyst has a tower structure, with 3-5 stacking layers; the stacking layer spacing is 0.2-2nm; and the stacking length is 3-6nm.
[0195] The temperature was lowered to 240°C, the pressure was lowered to 3.0 MPa, and the hydrogenation product after de-weighting and diene removal was introduced. The H2 / Oil molar ratio was 1000, and the raw material liquid phase volume space velocity was 0.8 h -1 .
[0196] The evaluation results of the catalyst are listed in Table 2.
[0197] Example 10
[0198] 1. Weigh 720g of ammonium metatungstate, 130g of ammonium molybdate, and 15g of lanthanum nitrate, dissolve in 500g of deionized water, add 57g of phosphoric acid, and stir at room temperature for 30 minutes to obtain aqueous solution I; weigh 250g of nickel nitrate and 42.5g of 1,2-cyclohexanediaminetetraacetic acid, dissolve in 200g of deionized water, and stir at room temperature for 30 minutes to obtain aqueous solution II, mix aqueous solution I and aqueous solution II, add 54g of ethylene glycol and 27g of 2-butanone, dilute to 1L with deionized water, and continue stirring at room temperature for 30 minutes to obtain solution III. The concentration of the Group VIB metal precursor in the solution III is 850g / L, the concentration of the Group VIII metal precursor is 250g / L, the molar ratio of the first auxiliary agent to the Group VIB metal atom is 1.0; the molar ratio of the second auxiliary agent to the Group VIII metal atom is 0.14. The mass ratio of ethylene glycol to 2-butanone in the third auxiliary agent is 2.
[0199] 2. Preparation of catalyst
[0200] Take 1000 g of Al2O3-TiO2-SiO2 carrier (including Al2O3, 97%, TiO2, 1.5%; SiO2, 1.5%) into a rotating pan, slowly add solution III prepared in 1, rotate the pan at 58 rpm, and soak for 10 minutes.
[0201] Curing: Curing the impregnated carrier at 30°C for 48 hours.
[0202] Drying, air atmosphere, starting at 25°C, heating at 10°C / hour to 70°C, maintaining constant temperature for 8 hours, heating at 10°C / hour to 110°C, maintaining constant temperature for 4 hours.
[0203] Calcination was carried out in air atmosphere, starting at 25°C, increasing the temperature at 140°C / hour to 445°C, and maintaining the temperature for 3 hours.
[0204] The catalyst composition is shown in Table 1.
[0205] 3. Catalyst sulfidation and evaluation
[0206] The catalyst prepared in 2 was loaded into a fixed bed reactor and sulfurization was started after the airtightness was qualified. Under the system pressure of 5.5 MPa, the hydrogen volume space velocity was 800 h -1 Hydrogen was introduced, and the temperature was raised from room temperature to 150°C at a rate of 30°C / h. A sulfurizing agent containing 0.5 wt% sulfur was introduced, and the temperature was raised to 180°C at a rate of 5°C / h for 6 hours, and then raised to 320°C at a rate of 10°C / h. The catalyst was kept at this temperature for 2 hours, and the catalyst was vulcanized. The catalyst after vulcanization was tested using a G2F30 transmission electron microscope (TEM) from FEI Company of the United States. Figure 7 From the figure, it can be seen that the number of stacking layers of the active phase of the sulfided catalyst is 3-10 layers; the stacking layer spacing is 0.2-2nm; and the stacking length is 3-12nm.
[0207] The temperature was lowered to 240°C, the pressure was lowered to 3.0 MPa, and the hydrogenation product after de-weighting and diene removal was introduced. The H2 / Oil molar ratio was 1000, and the raw material liquid phase volume space velocity was 0.8 h -1 .
[0208] The evaluation results of the catalyst are listed in Table 2.
[0209] Comparative Example 1
[0210] 1. Weigh 720g of ammonium metatungstate, 130g of ammonium molybdate, and 15g of lanthanum nitrate, dissolve in 500g of deionized water, add 57g of phosphoric acid, and stir at room temperature for 30 minutes to obtain aqueous solution I; weigh 250g of nickel nitrate and 42.5g of 1,2-cyclohexanediaminetetraacetic acid, dissolve in 200g of deionized water, and stir at room temperature for 30 minutes to obtain aqueous solution II, mix aqueous solution I and aqueous solution II, add 54g of ethylene glycol and 27g of cyclohexanone, and dilute to 1L with deionized water, and continue to stir at room temperature for 30 minutes to obtain solution III. The concentration of the Group VIB metal precursor in the solution III is 850g / L, the concentration of the Group VIII metal precursor is 250g / L, the molar ratio of the first auxiliary agent to the Group VIB metal atom is 1.0; the molar ratio of the second auxiliary agent to the Group VIII metal atom is 0.14. The mass ratio of ethylene glycol to cyclohexanone in the third auxiliary agent is 2.
[0211] 2. Preparation of catalyst
[0212] Take 1000 g of Al2O3-TiO2-SiO2 carrier (including Al2O3, 97%, TiO2, 1.5%; SiO2, 1.5%) into a rotating pan, slowly add solution III prepared in 1, rotate the pan at 58 rpm, and soak for 10 minutes.
[0213] Curing: Curing the impregnated carrier at 30°C for 48 hours.
[0214] Drying, air atmosphere, starting at 25°C, heating at 10°C / hour to 70°C, maintaining constant temperature for 8 hours, heating at 10°C / hour to 110°C, maintaining constant temperature for 4 hours.
[0215] Calcination was carried out in air atmosphere, starting at 25°C, increasing the temperature at 140°C / hour to 445°C, and maintaining the temperature for 3 hours.
[0216] The catalyst composition is shown in Table 1.
[0217] 3. Catalyst sulfidation and evaluation
[0218] The catalyst prepared in 2 was loaded into a fixed bed reactor and sulfurization was started after the airtightness was qualified. Under the system pressure of 5.5 MPa, the hydrogen volume space velocity was 800 h -1 Hydrogen was introduced, and the temperature was raised from room temperature to 150°C at a rate of 30°C / h. A sulfurizing agent containing 0.5 wt% sulfur was introduced, and the temperature was raised at 5°C / h for 6 hours to 180°C. After keeping the temperature constant for 5 hours, the temperature was raised at 5°C / h for 10 hours to 230°C. After keeping the temperature constant for 4 hours, the temperature was raised at 10°C / h for 5 hours to 280°C. After keeping the temperature constant for 4 hours, the temperature was raised at 10°C / h for 4 hours to 320°C. After keeping the temperature constant for 2 hours, the catalyst sulfurization was completed. The catalyst after sulfurization was tested using a G2F30 transmission electron microscope (TEM) from FEI Company of the United States. TEM Figure 6From the figure, it can be seen that the active phase of the sulfide catalyst is unevenly distributed, and only a very small amount forms a tower structure. A large amount of black components in the picture are caused by the agglomeration of active components.
[0219] The temperature was lowered to 240°C, the pressure was lowered to 3.0 MPa, and the hydrogenation product after de-weighting and diene removal was introduced. The H2 / Oil molar ratio was 1000, and the raw material liquid phase volume space velocity was 0.8 h -1 .
[0220] The evaluation results of the catalyst are listed in Table 2.
[0221] Comparative Example 2
[0222] 1. Weigh 720g of ammonium metatungstate, 130g of ammonium molybdate, and 15g of lanthanum nitrate, dissolve in 500g of deionized water, add 57g of phosphoric acid, and stir at room temperature for 30 minutes to obtain aqueous solution I; weigh 250g of nickel nitrate and 42.5g of 1,2-cyclohexanediaminetetraacetic acid, dissolve in 200g of deionized water, and stir at room temperature for 30 minutes to obtain aqueous solution II, mix aqueous solution I and aqueous solution II, dilute to 1L with deionized water, and continue stirring at room temperature for 30 minutes to obtain solution III. The concentration of the Group VIB metal precursor in the solution III is 850g / L, the concentration of the Group VIII metal precursor is 250g / L, the molar ratio of the first auxiliary agent to the Group VIB metal atom is 1.0; the molar ratio of the second auxiliary agent to the Group VIII metal atom is 0.14.
[0223] 2. Preparation of catalyst
[0224] Take 1000 g of Al2O3-TiO2-SiO2 carrier (including Al2O3, 97%, TiO2, 1.5%; SiO2, 1.5%) into a rotating pan, slowly add solution III prepared in 1, rotate the pan at 58 rpm, and soak for 10 minutes.
[0225] Curing: Curing the impregnated carrier at 30°C for 48 hours.
[0226] Drying, air atmosphere, starting at 25°C, heating at 10°C / hour to 70°C, maintaining constant temperature for 8 hours, heating at 10°C / hour to 110°C, maintaining constant temperature for 4 hours.
[0227] Calcination was carried out in air atmosphere, starting at 25°C, increasing the temperature at 140°C / hour to 445°C, and maintaining the temperature for 3 hours.
[0228] The catalyst composition is shown in Table 1.
[0229] 3. Catalyst sulfidation and evaluation
[0230] The catalyst prepared in 2 was loaded into a fixed bed reactor and sulfurization was started after the airtightness was qualified. Under the system pressure of 5.5 MPa, the hydrogen volume space velocity was 800 h -1Hydrogen was introduced, and the temperature was raised from room temperature to 150°C at a rate of 30°C / h. A sulfurizing agent containing 0.5 wt% sulfur was introduced, and the temperature was raised at 5°C / h for 6 hours to 180°C. After keeping the temperature constant for 5 hours, the temperature was raised at 5°C / h for 10 hours to 230°C. After keeping the temperature constant for 4 hours, the temperature was raised at 10°C / h for 5 hours to 280°C. After keeping the temperature constant for 4 hours, the temperature was raised at 10°C / h for 4 hours to 320°C. After keeping the temperature constant for 2 hours, the catalyst sulfurization was completed. The catalyst after sulfurization was tested using a G2F30 transmission electron microscope (TEM) from FEI Company of the United States to obtain TEM Figure 3 From the figure, it can be seen that the active phase distribution of the sulfided catalyst is extremely uneven, and there is no obvious tower structure.
[0231] The temperature was lowered to 240°C, the pressure was lowered to 3.0 MPa, and the hydrogenation product after de-weighting and diene removal was introduced. The H2 / Oil molar ratio was 1000, and the raw material liquid phase volume space velocity was 0.8 h -1 .
[0232] The evaluation results of the catalyst are listed in Table 2.
[0233] Comparative Example 3
[0234] 1. Weigh 100g of ammonium metatungstate, 60g of ammonium molybdate, and 15g of lanthanum nitrate, dissolve in 300g of deionized water, add 5g of phosphoric acid, and stir at room temperature for 30 minutes to obtain aqueous solution I; weigh 45g of nickel nitrate and 8.5g of 1,2-cyclohexanediaminetetraacetic acid, dissolve in 200g of deionized water, and stir at room temperature for 30 minutes to obtain aqueous solution II, mix aqueous solution I and aqueous solution II, add 10g of ethylene glycol and 5g of 2-butanone, dilute to 1L with deionized water, and continue stirring at room temperature for 30 minutes to obtain solution III. The concentration of the Group VIB metal precursor in the solution III is 110g / L, the concentration of the Group VIII metal precursor is 45g / L, the molar ratio of the first auxiliary agent to the Group VIB metal atom is 0.28; the molar ratio of the second auxiliary agent to the Group VIII metal atom is 0.157. The mass ratio of ethylene glycol to 2-butanone in the third auxiliary agent is 2.
[0235] 2. Preparation of catalyst
[0236] Take 1000 g of Al2O3-TiO2-SiO2 carrier (including Al2O3, 97%, TiO2, 1.5%; SiO2, 1.5%) into a rotating pan, slowly add solution III prepared in 1, rotate the pan at 58 rpm, and soak for 10 minutes.
[0237] Curing: Curing the impregnated carrier at 30°C for 48 hours.
[0238] Drying, air atmosphere, starting at 25°C, heating at 10°C / hour to 70°C, maintaining constant temperature for 8 hours, heating at 10°C / hour to 110°C, maintaining constant temperature for 4 hours.
[0239] Calcination was carried out in air atmosphere, starting at 25°C, increasing the temperature at 140°C / hour to 445°C, and maintaining the temperature for 3 hours.
[0240] The catalyst composition is shown in Table 1.
[0241] 3. Catalyst sulfidation and evaluation
[0242] The catalyst prepared in 2 was loaded into a fixed bed reactor and sulfurization was started after the airtightness was qualified. Under the system pressure of 5.5 MPa, the hydrogen volume space velocity was 800 h -1 Hydrogen was introduced, and the temperature was raised from room temperature to 150°C at a rate of 30°C / h. A sulfurizing agent containing 0.5 wt% sulfur was introduced, and the temperature was raised at 5°C / h for 6 hours to 180°C. After keeping the temperature constant for 5 hours, the temperature was raised at 5°C / h for 10 hours to 230°C. After keeping the temperature constant for 4 hours, the temperature was raised at 10°C / h for 5 hours to 280°C. After keeping the temperature constant for 4 hours, the temperature was raised at 10°C / h for 4 hours to 320°C. After keeping the temperature constant for 2 hours, the catalyst sulfurization was completed. The catalyst after sulfurization was tested using a G2F30 transmission electron microscope (TEM) from FEI Company of the United States to obtain TEM Figure 4 ,From the figure, it can be seen that the active components are scarce and the ,chips of a small amount of active components are distributed in a disorderly ,way.
[0243] The temperature was lowered to 240°C, the pressure was lowered to 3.0 MPa, and the hydrogenation product after de-weighting and diene removal was introduced. The H2 / Oil molar ratio was 1000, and the raw material liquid phase volume space velocity was 0.8 h -1 .
[0244] The evaluation results of the catalyst are listed in Table 2.
[0245] Table 1
[0246]
[0247]
[0248] Table 2
[0249]
[0250] The preferred embodiments of the present invention are described in detail above, but the present invention is not limited thereto. Within the technical concept of the present invention, the technical solution of the present invention can be subjected to a variety of simple modifications, including the combination of various technical features in any other suitable manner, and these simple modifications and combinations should also be regarded as the contents disclosed by the present invention and belong to the protection scope of the present invention.
Claims
1. A hydrogenation catalyst, characterized in that The catalyst comprises an active phase and a carrier, wherein the active phase comprises a metal element of Group VIB, a metal element of the lanthanide series and a metal element of Group VIII; After the catalyst is sulfided, the active phase presents a tower-shaped structure.
2. The hydrogenation catalyst according to claim 1, wherein The number of stacking layers of the tower structure is 3-10 layers, preferably 3-5 layers; and / or The stacking layer spacing of the tower structure is 0.2-2nm; and / or The stacking length of the tower structure is 3-12 nm, preferably 3-6 nm; and / or The mass content of the active phase in the catalyst is 15%-60%, preferably 18%-55%; the mass content of the carrier is 40%-85%, preferably 45%-82%; and / or The mass ratio of the metal element of Group VIB to the metal element of Group VIII in the active phase is 0.1-15, preferably 0.8-12, calculated as oxide; and / or The content of the lanthanide metal element in the active phase is 0.1-0.5 wt % in terms of oxide; Preferably, The Group VIB metal element is selected from Mo, W, Cr, preferably Mo and / or W; and / or The Group VIII metal element is selected from Fe, Co, Ni, Pt, Pd, preferably Ni and / or Co; and / or The lanthanide metal element is La and / or Ce; and / or The carrier is selected from at least one of Al2O3, Al2O3-TiO2, Al2O3-TiO2-SiO2, and Al2O3-SiO2, and is preferably selected from at least one of Al2O3, Al2O3-TiO2, and Al2O3-TiO2-SiO2.
3. A sulfided catalyst, characterized in that: The sulfided catalyst is obtained by sulfiding the hydrogenation catalyst according to claim 1 or 2; The active phase of the sulfidation catalyst has a tower-shaped structure; Preferably, The number of stacking layers of the tower structure is 3-10 layers, preferably 3-5 layers; and / or The stacking layer spacing of the tower structure is 0.2-2nm; and / or The stacking length of the tower structure is 3-12 nm, preferably 3-6 nm.
4. A method for preparing a hydrogenation catalyst, characterized in that: The method includes: (1) preparing a Group VIB metal precursor, a lanthanide metal precursor and a first auxiliary agent to form a solution I; preparing a Group VIII metal precursor and optionally a second auxiliary agent to form a solution II; mixing solutions I and II, and adding a third auxiliary agent to obtain a solution III; (2) Solution III is contacted with the carrier, cured, dried, and calcined; Wherein, the first auxiliary agent is an amino compound and / or an inorganic acid; the second auxiliary agent is an organic acid metal complexing agent; the third auxiliary agent is an alcohol and / or a ketone; The concentration of the Group VIII metal precursor in the solution III is above 45 g / L, and the concentration of the Group VIB metal precursor is above 140 g / L.
5. The preparation method according to claim 4, wherein The concentration of the Group VIII metal precursor in the solution III is 50-500 g / L, and the concentration of the Group VIB metal precursor is 150-850 g / L; Preferably, the ratio of the concentration of the Group VIII metal precursor to the concentration of the Group VIB metal precursor in the solution III is 0.1-1.2, more preferably 0.35-1.
0.
6. The preparation method according to claim 4 or 5, wherein: The first auxiliary agent is selected from at least one of urea, acetamide, ethylenediamine, ethanolamine, diethanolamine, triethanolamine, phosphoric acid, nitric acid, and sulfuric acid; and / or The second auxiliary agent is selected from at least one of 1,2-cyclohexanediaminetetraacetic acid, citric acid, tartaric acid, ethylenediaminetetraacetic acid, salicylic acid, and aminotriacetic acid; and / or The third auxiliary agent is a mixture of water-soluble alcohol and ketone, and preferably the mass ratio of the water-soluble alcohol to the ketone in the mixture is 0.05-2; more preferably, the third auxiliary agent is selected from a mixture of ethylene glycol and / or ethanol and acetone and / or 2-butanone.
7. The preparation method according to any one of claims 4 to 6, wherein: The molar ratio of the first auxiliary agent to the Group VIB metal atom is 0.1-1.2, preferably 0.25-1.0; and / or The molar ratio of the second auxiliary agent to the Group VIII metal atom is 0.05-1.2, preferably 0.14-0.
8.
8. The preparation method according to any one of claims 4 to 7, wherein: In step (2), the solution III is contacted with the carrier at a mass ratio of 0.5-2.5; preferably 1.0-2.0; and / or The carrier is selected from at least one of Al2O3, Al2O3-TiO2, Al2O3-TiO2-SiO2, and Al2O3-SiO2, preferably selected from at least one of Al2O3, Al2O3-TiO2, and Al2O3-TiO2-SiO2; and / or The Group VIB metal element is selected from Mo, W, Cr, preferably Mo and / or W; and / or The Group VIII metal element is selected from Fe, Co, Ni, Pt, Pd, preferably Ni and / or Co; The lanthanide metal element is La and / or Ce.
9. The preparation method according to any one of claims 4 to 7, wherein: The contact conditions include: The contact temperature is 0-60°C, preferably 20-40°C; and / or The contact time is 5-60 min, preferably 8-40 min; and / or The health-preserving conditions include: The curing temperature is 0-60°C, preferably 20-40°C; and / or The health-preserving time is 2-96h, preferably 6-48h; and / or The drying conditions include: The drying temperature is 50-130°C, preferably 60-120°C; and / or The drying time is 3-46 hours, preferably 6-36 hours; and / or Air volume airspeed 2-250h -1 , preferably 20-150h -1 ; and / or The conditions for the calcination include: The calcination temperature is 150-520°C, preferably 280-500°C; and / or The calcination time is 2-24 hours, preferably 3-12 hours; and / or Air volume airspeed 2-250h -1 , preferably 25-150h -1 .
10. Use of the hydrogenation catalyst according to claim 1 or 2 and / or the sulfided catalyst according to claim 3 and / or the catalyst prepared by the preparation method according to any one of claims 4 to 9 in crude oil hydrogenation, characterized in that: Before hydrogenation, the hydrogenation catalyst according to any one of claims 1 or 2 and / or the catalyst prepared by the preparation method according to any one of claims 4 to 9 is subjected to a sulfurization treatment; preferably, The hydrogenation conditions include: inlet temperature of 200-270°C, reaction pressure of 2.3-6.0MPa, hydrogen-to-oil volume ratio of 400-1500, liquid phase volume space velocity of 0.2-1.8h -1 ; and / or The vulcanization conditions include: the vulcanizing agent contains 0.05-2 wt% sulfur; and / or the vulcanization temperature is 120-380° C.; and / or the vulcanization time is 8-72 h; and / or the vulcanizing agent volume space velocity is 0.3-3 h -1 ; and / or hydrogen to oil volume ratio of 300-2000; and / or vulcanization pressure of 0.5-10.0MPa; Preferably, the vulcanization temperature is 150-360°C; and / or the vulcanization time is 8-56 hours; and / or the vulcanizing agent volume space velocity is 0.5-1.5h -1 ; and / or hydrogen to oil volume ratio of 500-1500; and / or vulcanization pressure of 1.0-6.0MPa; More preferably, the vulcanization is carried out in a programmed temperature manner, including: an initial temperature of 25-150°C, a heating rate of 5-15°C / min, a step temperature interval of 50-80°C, a step temperature holding time of 4-10h, a final temperature of 320-360°C, and a final temperature treatment time of 27-35h; and / or The raw material oil is selected from the product of ethylene tar after de-weighting and one-stage hydrogenation to olefins.
Citation Information
Patent Citations
Steeping solution and method for preparing catalyst by adopting steeping solution
CN102397796A
Preparation method for hydrorefining catalyst
CN102836725A
Co-impregnation liquid for preparing hydrocracking catalyst
CN1175481A
Methods of preparing bulk group VIII / group VIB metal catalysts
CN101553315A
Liquefied gas hydrogenating, olefin content decreasing and desulfurizing catalyst and preparation method thereof
CN102500403A